PENGARUH SUDUT DAN INTENSITAS CAHAYA DALAM PEMBACAAN OBJEK 3D PADA APLIKASI AUGMENTED REALITY - Mandarani, Putri; Yuliani, Riza; Syahrani, Anna (Jurnal EDik Informatika, 2020)
Augmented Reality (AR) applications that use 3D object tracking are still rarely used. This is because the appearance of information expected from a real object that is used as a marker is often slow and difficult to detect by the camera. The taking angle and lighting are part of many factors that influence marker detection. This study applies an experimental method by building an AR application using 3D object tracking by testing 2 variables, namely the angle and light intensity. The purpose of this study was to see the effect of light angles and intensity on the reading of 3D objects. The results obtained show that the effect of angle is inversely proportional to the magnitude of the light intensity. In other words, the appearance of 3D objects from the AR application is greatly influenced by conditions with bright light at a small angle. The level of light intensity is very influential on object detection. This can be seen from the average light flux (lumen) obtained, which is at an angle of 90° with lumen 205Cd. 3D object tracking applications can be used by the wider community in studying and getting to know building spatial plans.